Mastering Speaking English And Implementation of Communication Hospitality Skills on Museum Guide Service in Bandung - Indrianty, Septy; Riana, Nova (Institut Agama Islam Negeri Palopo, 2024)
The implementation of tourism requires the ability of good service providers in terms of interacting with visitors.Â Especially if the tourist destination is a destination that has the potential to receive guests/visitors from various nations. So in providing services to tourists, it is necessary to master English and Hospitality communication, which prioritizes hospitality. This study aims to determine the mastery of English and also the implementation of hospitality communication in museum guide services. The method used is descriptive qualitative by describing the depth of the data. Data collection was carried out in 3 ways: observation, interviews, and distributing questionnaires to 20 respondents consisting of museum guides and educators. The results of the study found that the guides' mastery of English in terms of the 4 speaking elements was in the